Efficacy of Pulsed UV-Light Treatment on Wastewater Effluent Disinfection and Suspended Solid Reduction - Uslu, Gulsad; Demirci, Ali; Regan, John M. (Asce-Amer Soc Civil Engineers, 2015)
Disinfection of municipal wastewater effluents is a critical component of water pollution control. To achieve this, novel alternative disinfection technologies have been getting attention recently such as pulsed ultraviolet (UV) light, which can be used to inactivate microorganisms in a short time. Therefore, the research reported in this paper was undertaken to determine the efficacy of pulsed UV light for inactivation of Escherichia coli and Bacillus subtilis spores, in synthetic and real municipal wastewater effluent. The results with synthetic municipal wastewater effluent demonstrated that complete inactivation was obtained with an 8-cm sample distance, 30-mL sample volume, and 15-s time combination for E. coli [8.53log10 colony-forming units (CFUs)/mL reduction], whereas a 15-mL sample volume (with the same sample distance and treatment time) was required for B. subtilis (7.57log10CFU/mL reduction) at total energy dose of 10.9J/cm2. A response surface model was developed to predict the inactivation for E. coli and B. subtilis spores. Using sterilized real wastewater effluent with the same experimental conditions of an 8-cm distance and 30-mL volume for E. coli, and 8-cm distance and 15-mL volume for B. subtilis, complete inactivation required the same 15-s treatment for E. coli, but 20-s treatment for B. subtilis. In addition, a 2.5, 5, 10, 15, and 25% (volume/volume) E. coli or B. subtilis inoculum was added to the synthetic municipal wastewater effluent, and treated by pulsed UV-light for 5-45s. Results showed that pulsed UV treatment at the optimum conditions increased suspended solids removal by 26.5 and 21.45%, for E. coli and B. subtilis, respectively. Overall, the results of the research reported in this paper clearly demonstrated the complete inactivation of vegetative cells or spores in municipal wastewater effluents, and further demonstrated the reduction of suspended solids, suggesting that pulsed UV light has the potential to be used for disinfection of municipal wastewater effluent.
Keywords: Pulsed ultraviolet (UV) light; Inactivation; Sanitation; Wastewater; Response surface modeling; E; coli; B; subtilis